Sosialisasi dan Strategi Personal Selling Penerimaan Mahasiswa Baru Fakultas Ekonomi dan Bisnis Iain Palangkaraya dalam Kondisi Pandemi Covid-19 - Sofyan Hakim; Arif Mubarok; Hilmi Satria Himawan; Hanief Monady (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
COVID-19 has hit the world and has had a major effect on all activities and sectors of the community's economy in the world. This impact also affects state universities' ability to recruit new students, so it requires a strategy to be able to compete with other universities. This research was conducted to determine the strategy carried out by the Faculty of Economics and Business at the Islamic State University of Palangka Raya to attract new students using descriptive-qualitative methods. Data to support this research is sourced from primary data obtained through interviews with the parties concerned and secondary data obtained from various data and documents. This research refers to the theory of personal selling strategies, which includes four strategy processes, namely: attention stage, interest stage, desire stage, and action stage, based on the results of interviews, observations, and other data collection. The results of this socialization show that the campus in accordance with its strategy of netting new students is applying an excellent process.